Anomaly Detection: An Application of Visual Surveillance (International Journal of Engineering and Computer Science, 2017)
Recent advances in camera and video technologies have made it possible to network numerous video cameras together in order to provide visual coverage of extensive public spaces such as airports and train stations. As the size of the camera network grows and the level of activity in the public space increases, it becomes infeasible for human operators to monitor the multiple video streams and identify all events of possible interest. Consequently, a timely challenge for computer vision researchers is to design camera sensor networks capable of performing visual surveillance tasks automatically or at least with minimal human intervention. This paper presents with the technology of intelligence of the surveillance systems, while surveillance systems can provide many services, this paper describes the development of an application that uses cameras to detect the changes in the homes, buildings and offices etc. Basically the proposed system will detect the changes (whenever anybody enters) in a room with the help of the motion detection algorithm and it will automatically send an email to a computer in a security room.